Experiencing an art education program through immersive virtual reality or iPad: Examining the mediating effects of sense of presence and extraneous cognitive load on enjoyment, attention, and retention - Tang, Qingyang; Wang, Yanyun; Liu, Hao; Liu, Qian; Jiang, Shen (Frontiers in Psychology, 2022)
Sense of presence and extraneous cognitive load are the two psychological effects widely employed to explain the cognitive outcomes caused by high-immersive media (e.g., virtual reality). This study identified the concepts of both technological affordance (i.e., immersion) and psychological effects of VR learning, and investigated the mechanism by which immersion leads to better or worse communication in the context of art education. We operationalized the concept of immersion into two levels: a high-immersive VR system (HTC VIVE Cosmos) and a low-immersive tablet system (iPad). Through a between-subject experiment, we found that higher immersion led to higher sense of presence, but lower extraneous cognitive load. Enjoyment and attention increased as sense of presence rose, but were not necessarily predicted by extraneous cognitive load. This study mainly indicated that sense of presence was a more robust explanatory variable than extraneous cognitive load, and cognitive load could be lower in high-immersive environment with content designed for VR specifically.